Acute Kidney Injury Caused by Obstructive Nephropathy - Jonathan S Chávez-Iñiguez; Goretty J Navarro-Gallardo; Ramón Medina-González; Luz Alcantar-Vallin; Guillermo García-García (International Journal of Nephrology)
Acute kidney injury secondary to obstructive nephropathy is a frequent event that accounts for 5 to 10% of all acute kidney injury cases and has a great impact on the morbidity and mortality in those affected. The obstruction in the urinary tract has a profound impact on kidney function due to damage produced by ischemic and inflammatory factors that have been associated with intense fibrosis. This pathology is characterized by its effects on the management of fluids, electrolytes, and the acid-base mechanisms by the renal tubule; consequently, metabolic acidosis, hyperkalemia, uremia, and anuria are seen during acute kidney injury due to obstructive nephropathy, and after drainage, polyuria may occur. Acute urine retention is the typical presentation. The diagnosis consists of a complete medical history and should include changes in urinary voiding and urgency and enuresis, history of urinary tract infections, hematuria, renal lithiasis, prior urinary interventions, and constipation. Imaging studies included tomography or ultrasound in which hydronephrosis can be seen. Management includes, in addition to drainage of the obstructed urinary tract system, providing supportive treatment, correcting all the metabolic abnormalities, and initiating renal replacement therapy when required. Although its recovery is in most cases favorable, it seems to be an undervalued event in nephrology and urology. This is because it is mistakenly believed that the resolution and recovery of kidney function is complete once the urinary tract is unobstructed. It can have serious kidney sequelae. In this review, we report the epidemiology, incidence, pathophysiological mechanisms, diagnosis, and treatment of acute kidney injury due to obstructive nephropathy.